Simultaneous management of aortic and mitral regurgitation through one-stage transcatheter aortic valve replacement and transcatheter edge-to-edge repair: case report - Lin, Hao; Zhu, Mei; Lv, Meng; Wang, Zhengjun (Frontiers in Cardiovascular Medicine, 2024)
This case report presents a 72-year-old male patient who presented with exertional dyspnea for over 10 years, which had progressively worsened over the past 4 months. Transthoracic echocardiography revealed severe aortic and mitral regurgitation, with a left ventricular ejection fraction of 37% and a left ventricular end-diastolic diameter of 64 mm. Despite receiving long-term optimal medical management, there was no improvement in symptoms or severity of valvular regurgitation. Given the relatively high surgical risk associated with double valve replacement in this elderly patient and his preference for minimally invasive procedures, a one-stage transapical aortic valve replacement and transcatheter mitral valve repair using the edge-to-edge technique were planned. The patient was discharged 8 days post-procedure without any complications. At 1-month follow-up, the patient's New York Heart Association (NYHA) functional class had improved to grade II.